Software architecture of the system for expert assessment of the efficiency of unmanned aviation systems - Ostroumov, I.V.; Ivashchuk, O.R.; Kuzmenko, N.S.; Svirko, V.O. (Problems of Informatization and Management, 2025)
This paper proposes a software architecture of an automated system for expert assessment of the quality of unmanned aviation systems, designed to collect individual expert assessments, their statistical processing and generation of interactive reports and recommendations for improving the ergonomic characteristics of UAS. The program allows you to systematize expert assessment of the quality of unmanned aviation systems when direct measurements are impossible or ineffective. The program is implemented on the basis of a cross-platform Web solution with a client part in HTML5/JavaScript and server processing in PHP, the modular structure of the system is given (user account, project creation, expert evaluation module, data analysis, reports and recommendations), approaches to data storage and protection, authentication mechanisms and an algorithm for aggregating results based on a weighted average are described. Functional capabilities for dynamically adjusting weights and thresholds are proposed, as well as tools for ensuring the integrity and accessibility of examination results. The final part of the work provides an example of software implementation and its interface.